Case Report: Rhabdomyolysis in aneurysmal subarachnoid hemorrhage: A rare case with implications for management - Liao, Gang; Chen, Kang; Xu, Jiang; Wang, Chunliang (Frontiers in Surgery, 2023)
Background: In recent years, some cases of rhabdomyolysis after surgery have been reported. In this report, we present an adult patient with rhabdomyolysis after intracranial aneurysm surgery. Case Report： A 59-year-old male suffered from a coma, fever, and soy sauce urine after intracranial aneurysm clipping. A routine blood examination showed that liver and kidney function were impaired, and creatine phosphokinase(CK) and creatine phosphokinase isoenzyme(CK-MB) levels increased. Therefore, we consider patients with rhabdomyolysis after intracranial aneurysm surgery. A series of treatment schemes, such as intravenous fluid infusion, alkalized urine, and hemodialysis, were adopted immediately, and finally the patient was discharged safely. Conclusion：For some postoperative patients, once the level of CK/CK-MB increases, acute renal damage occurs, and the urine color turns soy sauce, we should be alert to postoperative rhabdomyolysis.For those patients who have been diagnosed with rhabdomyolysis, we need to take timely treatment measures to avoid an unfortunate occurrence.